The Effect of Femoral Malrotation in Offset Templating for Total Hip Arthroplasty: A Cadaveric Study and Curvilinear Analysis - Schutte, Harold Del, Jr.; Navarro, Sergio M.; Shaikh, Hashim; Barfield, William R.; Conrad, Jeffrey; Romero, Neil; McTighe, Tim (The Journal of Hip Surgery, 2021)
Techniques allow assessment of preoperative offset in hip arthroplasty. This study assessed femoral rotation in preoperative offset templating using a cadaveric model. Ten femurs were imaged at degrees of rotation. Offset was measured. A generalizable equation predicting change in offset was derived with a curvilinear model. Statistically significant differences at rotational positions were found. For 30 degrees of internal rotation, 2.1 mm change in adjusted mean offset existed; for 30 degrees of external rotation, 8.4 mm change existed. Improved awareness of malrotation of the proximal femur and templating adjustments may improve total hip arthroplasty outcomes. This study reflects level of evidence III.
Keywords: femoral offset; cadaveric study; total hip arthroplasty; templating